Daikenchuto, a Traditional Kampo Medicine, Facilitates Mucosal Hyperemic Responses through Activation of TRPA1- and TRPV1-Expressing Sensory Nerves in Rat Stomach - Yoshikubo, Masatoshi; Tashima, Kimihito; Raimura, Masaki; Watanabe, Yuto; Noma, Yukiko; Horie, Syunji (Planta Medica International Open, 2022)
Daikenchuto is a traditional Kampo medicine used to treat cold sensations and dysmotility in the abdomen. This study investigated the roles of transient receptor potential ankyrin 1- and transient reporter potential vanilloid 1-expressing sensory nerves in daikenchuto-induced gastric mucosal blood flow by pharmacological and immunohistochemical analyses using male Sprague-Dawley rats. Gastric mucosal blood flow was measured in ex vivo stomachs using a laser Doppler flowmeter. Transient receptor potential ankyrin 1 activator allyl isothiocyanate or transient reporter potential vanilloid 1 activator capsaicin were applied for 10 min, and daikenchuto was applied for 10 or 30 min to the rat stomach. Transient reporter potential vanilloid 1 blocker N-(4-t-butylphenyl)-4-(3-chlopyridin-2-yl) tetrahydropyrazine-1(2H)-carboxamide and transient receptor potential ankyrin 1 blocker A-967079 were also administered intragastrically. Capsaicin and allyl isothiocyanate increased gastric mucosal blood flow immediately after the intragastric application, which was almost completely inhibited by N-(4-t-butylphenyl)-4-(3-chlopyridin-2-yl) tetrahydropyrazine-1(2H)-carboxamide and A-967079, respectively. Daikenchuto increased gastric mucosal blood flow in a concentration-dependent manner. A-967079 significantly inhibited the increase in gastric mucosal blood flow induced by daikenchuto. In contrast, N-(4-t-butylphenyl)-4-(3-chlopyridin-2-yl) tetrahydropyrazine-1(2H)-carboxamide inhibited the responses to daikenchuto only in the late phase but not in the initial phase. Interestingly, in the deafferentation of capsaicin-sensitive sensory fiber in rats, the increased gastric mucosal blood flow induced by daikenchuto was only decreased in the late phase. Although transient receptor potential ankyrin 1- and transient reporter potential vanilloid 1-immunoreactive fibers were observed around the submucosal blood vessels of normal subjects, they were completely absent in the deafferentation of capsaicin-sensitive sensory fibers. Thus, daikenchuto increases gastric mucosal blood flow via transient receptor potential ankyrin 1- and transient reporter potential vanilloid 1-co-expressing sensory nerves in rat stomachs.
Keywords: daikenchuto; gastric mucosal blood flow; TRPA1; TRPV1; sensory nerves; rat